STUDI KELAYAKAN WADUK CIKAWARI 2A DAN 5A DALAM RANGKA PEMENUHAN KEBUTUHAN AIR KOTA BANDUNG - Cleon Christopher; Doddi Yudianto; Albert Wicaksono (JURNAL TEKNIK HIDRAULIK, 2021)
The water need in the Northern area of Bandung City was predicted to be 2.49 m3/s in 2040. The government responded to this issue by planning the construction of several reservoirs in the Cikapundung watershed. A previous study suggested three potential locations, i.e., Cikukang 2, Cikawari 2A, and Cikawari 5A reservoir. Since Cikawari 2A and Cikawari 5A are located on the same Cikawari river, three construction alternatives, i.e., a single reservoir of Cikawari 2A, a single reservoir of Cikawari 5A, and cascade reservoir Cikawari 2A+5A are proposed. Each alternative has its own advantages and limitations, thus evaluation of the best construction alternative needs to be carried out. The evaluation was conducted based on their reliable service in supplying water to Bandung City. This evaluation was analyzed by comparing the projected water demand following population growth and water availability derived from the rainfall-runoff model, NRECA. The analysis was conducted using two variations of dam height and reservoir capacity for each alternative. Based on the analysis results, the single reservoir of Cikawari 2A with 45 m of dam’s height was chosen as the most suitable alternative. It can supply 0.56 m3/s of water and provide water for 30.4% of the citizens in 2020, and decrease to 30.15% in 2040. However, it was also found that the reservoir could only supply 0.44 m3/s of water during the dry period. These results showed that the construction of the reservoir itself could not meet the total water demand. Therefore, another alternative is required to closing the gap in water demand.Keywords: Cikapundung watershed, water supply, Cikawari reservoir, reservoir simulation, service reliability